2011
DOI: 10.1093/annonc/mdq716
|View full text |Cite
|
Sign up to set email alerts
|

Tumor–ratio–metastasis staging system as an alternative to the 7th edition UICC TNM system in gastric cancer after D2 resection—results of a single-institution study of 1343 Chinese patients

Abstract: The novel TRM staging system predicts survival of gastric cancer more accurately than the 7th edition TNM system. It may be considered as an alternative to TNM system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
88
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 29 publications
4
88
0
1
Order By: Relevance
“…To evaluate the rN staging system, some previous reports excluded patients with fewer than 16 LNs retrieved [16,20,22]; some researchers preferred the patients treated by limited lymphadenectomy, [9,10,18,23]; and some centers evaluated the rN system as an independent prognostic factor in gastric cancer regardless of the type of lymphadenectomy, or in both [15 and B15 LNs examined [17,19,24,25], as we did in our report. All the reports indicated that the rN staging system has superiority in prognosis assessment compared with the traditional AJCC pN system.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…To evaluate the rN staging system, some previous reports excluded patients with fewer than 16 LNs retrieved [16,20,22]; some researchers preferred the patients treated by limited lymphadenectomy, [9,10,18,23]; and some centers evaluated the rN system as an independent prognostic factor in gastric cancer regardless of the type of lymphadenectomy, or in both [15 and B15 LNs examined [17,19,24,25], as we did in our report. All the reports indicated that the rN staging system has superiority in prognosis assessment compared with the traditional AJCC pN system.…”
Section: Discussionmentioning
confidence: 87%
“…However, there is much controversy regarding the most appropriate cutoff ratio because the ratios differ among investigators. The following cutoff values have been proposed: 0, 0.20, 0.50 [10,24], 0, 0.30, 0.60 [15,25], 0, 0.10, 0.25 [9,16,20], 0, 0.30, 0.70 [17], 0, 0.015, 0.40 [23], 0, 0.10, 0.25 [19], 0, 0.25, 0.50 [18], and 0, 0.10, 0.40 [22]. The cutoff values showed great variety in different countries, even in different centers in the same country.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in China proved a better prognostic stratification for the new actualized version [1]. Another study from Korea showed similar results for the new TNM system, proving a more detailed prognostic assessment, especially between T2 and T3 and N1 and N2 tumors [2].…”
mentioning
confidence: 72%
“…Previous studies have demonstrated that the effects of LNR staging is superior to that of pN staging in predicting prognosis of patients for many cancer sites: colon (Chen et al, 2011), gastric (Wang et al, 2011;Yu et al, 2011), pancreas (Pawlik et al, 2007;Keck et al, 2012), esophagus (Greenstein et al, 2008), corpus uteri (Chan et al, 2007) and bladder (Herr, 2003).…”
Section: Discussionmentioning
confidence: 99%